2020
DOI: 10.3389/fmolb.2020.563142
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Common Genes Related to Platelet and Immunity for Lung Adenocarcinoma Prognosis Prediction

Abstract: Background: Although 1000s of immune-related and platelet receptor-related genes have been identified in lung adenocarcinoma, their role in prognosis prediction remains unclear.Methods: We downloaded mRNA data from the Cancer Genome Atlas Dataset (TCGA), and GSE68465 or GSE14814 data sets from the Gene Expression Omnibus (GEO) database. Results:The high-risk group's overall survival (OS) time was lower than that of the lowrisk group's in TCGA (p = 1.15e-03). Additionally, the risk score was an independent prog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…High expression of CCNA2 was connected with the poor OS in LIHC ( Li et al, 2021a ) and PRAD ( Feng et al, 2021 ). CCNA2 expression was an essential component of the prognostic model in LUAD ( Zhou et al, 2020 ), LUSC ( Gao et al, 2020 ) and KIRC ( Zhan et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…High expression of CCNA2 was connected with the poor OS in LIHC ( Li et al, 2021a ) and PRAD ( Feng et al, 2021 ). CCNA2 expression was an essential component of the prognostic model in LUAD ( Zhou et al, 2020 ), LUSC ( Gao et al, 2020 ) and KIRC ( Zhan et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Some other interesting and relevant discoveries include the significant correlation between CCNA2 expression and MLH1, MSH2, MSH6, PMS2, and EPCAM, suggesting that CCNA2 may be involved in tumor-related developmental processes including signaling, migration, and proliferation [40,41]. Zhou et al found that CCNA2 is a potential diagnostic and prognostic biomarker for LUAD, and CCNA2 expression positively correlated with immunity therapy efficiency in LUAD [42]. Chen et al also confirmed that CCNA2 is involved in hypoxia signature affecting the clinical outcomes and immune microenvironment of ACC [43].…”
Section: Discussionmentioning
confidence: 99%
“…8,49,50 The ANAPC1 protein in the ubiquitin-proteasome pathway is a cell cycle-regulating E3 ubiquitin ligase, which promotes cancer progression by controlling mitosis and the G1 phase of the cell cycle, and high ANAPC1 was associated with poor prognosis. 51,52 Furthermore, another ubiquitinproteasome pathway gene, PSMD2, regulates cancer cell proliferation and cell cycle progression by modulating proteasome degradation, which is positively correlated with poor prognosis. 53,54 In this study, the expression levels of ANAPC1 and PSMD2 were decreased…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, a molecular‐based prognosis model and risk stratification are needed to further improve prediction accuracy for patients with TCL and T‐ALL 8,49,50 . The ANAPC1 protein in the ubiquitin–proteasome pathway is a cell cycle‐regulating E3 ubiquitin ligase, which promotes cancer progression by controlling mitosis and the G1 phase of the cell cycle, and high ANAPC1 was associated with poor prognosis 51,52 . Furthermore, another ubiquitin–proteasome pathway gene, PSMD2, regulates cancer cell proliferation and cell cycle progression by modulating proteasome degradation, which is positively correlated with poor prognosis 53,54 .…”
Section: Discussionmentioning
confidence: 99%